Literature Review on Farmers’ Perception Towards Information &Communication Technology (ICT) - Rani, Seema; Kaur , Simranjit (Gyan Management Journal, 2019)
The role of Information & Communication Technology (ICT) is important to educate the farmers about the agriculture productivity and the agriculture market. The farmers are not able to access the market properly but ICT provides the helps to the farmers to improve their marketing skills. The ICT is the important pillar of the communication transfer to the farmers. The various studies have examined the perception of the farmers towardsInformation & Communication Technology (ICT). The paper intends to review the literature on Information & Communication Technology (ICT). The present study focuses on the conceptual framework about the farmers’ perception towards ICT.